2019
DOI: 10.1007/s42729-019-00129-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biochar Changed the Status of Nutrients and Biological Activity in a Calcareous Soil

Abstract: Low nutrient availability and biological activity are the main challenges in calcareous soils with low organic matter (OM) content. The purpose of the present study was to evaluate the responses of soil nutrient status and biological traits to addition of corn residue biochar produced at different pyrolysis temperature in a calcareous soil. Biochars were made at 200 (BC200), 350 (BC350), and 500°C (BC500), added to a calcareous soil at 1 and 2% (w/w) and were incubated for 90 days. The application of biochars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 45 publications
9
55
0
1
Order By: Relevance
“…Therefore, the application of the biochars used in this study caused a significant increase in soil SOC content. Our results agreed with the findings of Karimi et al (2020), who reported that the addition of corn biochar increased the SOC content of calcareous soil under incubation conditions. Saffari et al (2020) also reported that the SOC content in a sandy loam soil Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the application of the biochars used in this study caused a significant increase in soil SOC content. Our results agreed with the findings of Karimi et al (2020), who reported that the addition of corn biochar increased the SOC content of calcareous soil under incubation conditions. Saffari et al (2020) also reported that the SOC content in a sandy loam soil Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In other work, Karimi et al (2020) also reported that a significant increase in the pH of calcareous soil that was amended with corn-residue biochar. The biochars used in the current study had a high carbon content (Table 2).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…According to the results, which are similar to our previous study, biochars would alter the metals' distributions in a way that they declined readily available forms (exchangeable, associated with carbonates, and associated with Fe-Mn oxides), but raised less reachable sites (associated with organic matter and residuals) in the soil (Kabiri et al 2019). Similarly to the present research, Karimi et al (2020) reported that the application of 2% corn residue biochar produced at 500°C decreased DTPA-Zn in a calcareous soil. In other work, Karimi et al (2019) reported that the application of corn residue biochar produced at 500°C increased Zn associated with organic matter and residual fraction in calcareous soil, while exchangeable and associated with Fe-Mn oxide fractions decreased.…”
Section: Znsupporting
confidence: 90%
“…The biochar amendment increase the organic carbon, microbial biomass carbon at 1.20 to 2.24 folds, microbial respiration at 1.21 to 2.23 folds, dehydrogenase activity at 1.47 to 2.30 folds and catalase activity at 1.80 to 2.93 folds. But the pyrolysis temperature and rate of application influence the biological properties of soil [65]. The different kinds of biochar have varied physical and chemical properties that conjunction with different soil ecosystem causes the varying level of microbial responses to amend of biochar in soils.…”
Section: Fig 2 Factors Influencing the Impacts Of Biochar On Soil Pmentioning
confidence: 99%